2021
DOI: 10.20944/preprints202104.0702.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability of Vaccination Against COVID-19 Among Selected Residents of the Cities of Caloocan, Malabon, and Navotas, Philippines

Abstract: With COVID-19 vaccines slowly being rolled out in many countries, it is important to understand the public’s acceptance of being vaccinated. This study aims to study the willingness and motivations among residents of the cities of Caloocan, Malabon, and Navotas, Philippines to be vaccinated against COVID-19. Based on an online survey of 137 respondents, who willingly participated in the study, 71% will take a COVID-19 vaccine if it becomes available, with similar rates among respondents from Caloocan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The result showed that Filipinos were much aware of the different types of vaccine, especially the mRNA-based vaccine of Pfizer and Moderna. Comirnaty (Pfizer) is the only brand that more than half of the respondents (59%) are familiar with, according to [44], followed by mRNA-1273 (Moderna). As a result, it's safe to assume that the responders were well-versed in the concept of an mRNA-based vaccine.…”
Section: Knowledge Of the Respondents About Covid-19 Vaccinementioning
confidence: 99%
“…The result showed that Filipinos were much aware of the different types of vaccine, especially the mRNA-based vaccine of Pfizer and Moderna. Comirnaty (Pfizer) is the only brand that more than half of the respondents (59%) are familiar with, according to [44], followed by mRNA-1273 (Moderna). As a result, it's safe to assume that the responders were well-versed in the concept of an mRNA-based vaccine.…”
Section: Knowledge Of the Respondents About Covid-19 Vaccinementioning
confidence: 99%
“…Vaccine hesitancy has been reported across various population groups in the Philippines despite genuine efforts to advocate for the COVID-19 vaccine. [5][6][7] The study sites apply a trimedia strategy for vaccine advocacy: disseminating information on TV, radio, and social media. Health education activities also occur at the community level, including having conversations with the vaccine hesitant then providing them with correct information.…”
Section: Vaccine Hesitancy Is a Central Issue To Vaccination Demand A...mentioning
confidence: 99%
“…An array of rationalizations emanating from sociocultural and digital media influences contribute to vaccine hesitancy, consistent with findings from broader literature. 5,6,[8][9][10] Some HCWs refuse vaccination to avoid the injection of substances not part of their natural immunity. Another issue is that while younger members of a family may want to be vaccinated, it is culturally unacceptable to go against the opinion of elders who are likely vaccine hesitant.…”
Section: Vaccine Hesitancy Is a Central Issue To Vaccination Demand A...mentioning
confidence: 99%